A Female-Male Net Nutrition Comparison Using Differences-in-Decompositions: Late 19th and Early 20th Century Social Feminism and Women's Suffrage - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2019)
When other measures for economic welfare are scarce or unreliable, the body mass index (BMI) is a biological measure that reflects current net nutrition. This study uses a difference-in-decompositions framework to analyze how women's BMIs varied with the advent of early 20th century social feminism. Late 19th and early 20th century US economic development improved the relative status of women relative to both men before and after the transition to social feminism. Twentieth century women's BMIs were higher than 19th century women relative to men with the rise of social feminism. The primary source of female-male across-group variation was height and nativity, indicating there was net nutritional progress for women relative to men associated with changing cumulative net nutrition. The primary source of female-male within-group variation was nativity and socioeconomic status, indicating there was net nutritional progress relative to women born before the transition for women born after the rise of social feminism association with socioeconomic status.
Keywords: C10; C40; D10; I10; N30; 330; BMI variation; economic transitions Oaxaca decompositions